The social housing and the experience of the U.N.L's Social Institute - Acosta, María Martina (Universidad Nacional de Mar del Plata. Facultad de Arquitectura, Urbanismo y Diseño, 2003)
The 1930s represents the moment in which the architecture, as a discipline, defines and adjusts a field of activity. On the bases of its own definition, the housing outlines itself in a novel manner: it desplace itself from the orbit of the hygenism and the moral critic exercised by doctors, lawyers, teachers or priests, to a contour which transforms it in object of its own specificity. However, in Santa Fe, the early presence of the Industrial Superior School confers to technicians a space which, during the 1930s, will give as a result a new quantity of houses, renovating the image of the city and conforming a qualified texture. This work analyzes the action of the U:N:L's Social Institute and the concourse convoked in 1935 about social - urban and rural - housing which invites only constructor technicians for being considered the most appropriate ones for solving this kind of problem.